The Thermochemical Deposition Approach was used to Manufacture a Lead Sulphide Composite Membrane, which exhibits Optical and Synthetic Properties - Atyaf Sarhan Farhan Alrubaie (Peerian Journals Publishing, 2024)
This study involved the preparation of thin films of lead sulphide compound with three different thicknesses (150, 250, and 350 Nm) using pure materials of lead sulphate compounds, lead nitrate solution, and thiourea solution. The films were created through thermochemical deposition at a temperature of 623 K. Laboratory tests were conducted to determine the characteristics of the membranes, including the crystalline nature derived from lead sulphide and the cubic type with a diffraction pattern (200). Additionally, the membranes were analysed using an atomic force microscope, which revealed a decrease in the average square root and surface roughness. The findings demonstrated a positive correlation between the thickness of the lead sulphide membrane and the optical energy gap. This research aimed to assist researchers in the field of thin films by providing insights into the crystalline properties of lead sulphide membranes. These membranes hold significant value in scientific research, reagent applications, and the production of solar cells.
Keywords: Lead sulfide membranes; Optical energy gap; Thermochemical deposition